Peningkatan Literasi Matematis dalam Pembelajaran Matematika melalui Model Problem Based Learning pada Siswa Kelas XI - Devy Asfira Fitriani; Rini Setyaningsih (Departement of Mathematics Education, 2024)
This research is motivated by the low mathematical literacy abilities of students in learning the topic of circles in mathematics. The aim of this research is to explore how the problem-based learning model affects the improvement of mathematical literacy skills in eleventh grade students. This research is a Classroom Action Research consisting of four stages. The location of this research is at SMA Muhammadiyah 3 Surakarta, in the eleventh grade science class. In this study, the chosen method is qualitative research adopting the problem-based learning approach to the topic of circles. Data collection techniques consist of observation and tests. Observation is conducted to monitor the development of students during the learning process, while tests are used to measure students' mathematical literacy skills. In the pre-cycle, it was found that the level of students' mathematical literacy ability was still quite low at 47%. In cycle I, there was an improvement, reaching 65%, and then in cycle 2, a fairly good mastery level was achieved, with a percentage of 81%. Thus, the Problem-Based Learning model is appropriate for teaching mathematics on the topic of circles to enhance students' mathematical literacy skills